In vitro multiplication of Toxoplasma gondii and Trypanosoma cruzi in mouse, rat and hamster astrocytes - Troyo Rodríguez, Adriana (2003)
The infection and multiplication of Toxoplasma gondii and Trypanosoma cruzi were compared in primary cultures of white rat, mouse and hamster astrocytes. These cells were cultured on cover slides and infected with T. gondii tachyzoites or T. cruzi blood trypomastigotes. Results show that hamster astrocytes are more susceptible to the multiplication of both parasites than rat and mouse cells. There was no statistical difference between the T. gondii infection in rat and mouse astrocytes (p < 0.05), and this suggests an important role of other mechanisms or cells in the white rat natural resistance to this parasite. Because the hamster astrocytes are less resistant to these parasites multiplication and not necessarily to the invasion, any difference observed could be due to an intracellular effect: hamster brain astrocytes favor survival and multiplication of these parasites.